Perkembangan Sekolah Guru: Hoogere Kweekschool Purworejo Tahun 1914-1930 - Soniadewi, Nazhiifah Nuur'ainii; Charismana, Dian Satria (UIN Sunan Gunung Djati Bandung, 2024)
This study examines the establishment and development of Hoogere Kweekschool in Purworejo between 1914 and 1930, emphasizing its role in shaping the educational landscape in colonial Indonesia. During the early 20th century, education in Indonesia remained inaccessible for the majority, with opportunities restricted to elite circles, primarily to fulfill colonial administrative needs. The founding of HKS marked a significant step in expanding access to advanced teacher training for local youth, aligning with the colonial government's Political Ethical Policy aimed at improving education for indigenous populations. HKS Purworejo, designed to train graduates of kweekschools into highly skilled teachers, offered advanced curricula including pedagogy, Dutch language, mathematics, and general sciences. Using historical research methods, this study explores primary and secondary sources to assess the institution's influence. Findings reveal that HKS Purworejo not only fulfilled colonial labor demands but also contributed significantly to the intellectual and social awakening of Indonesians, laying foundations for the post-independence education system. The study underscores the dual role of colonial education as both an instrument of exploitation and a pathway to empowerment.